Exploring rape myth acceptance among general medical practitioners in South Africa - Liountris, Demitri (2021)
Rape myths have several negative effects on society, and can affect those who come into contact with victims of sexual assault on a professional level. One group of professionals that assist victims are general medical practitioners and in a country like South Africa, that has a high rate of rape, it is not uncommon for general medical practitioners to find themselves assisting victims. Previous research has suggested that professionals who assist victims such as police officers and lawyers are susceptible to rape myth acceptance. In South Africa, research suggests that medical health professionals can have negative views of victims, depending on a number of factors such as the victim's behaviour and alcohol consumption. Presenting data collected using the Illinois Rape Myth Acceptance Scale (IRMAS) from a sample of 44 general medical practitioners in South Africa, it was found that the participants had low levels of rape myth acceptance. The findings indicated that not only were rape myths not strong influences within the sample, myths that related to the concept of ‘real rape' were the least likely to be supported. Furthermore, additional questions in the survey revealed that general medical practitioners are not well-equipped to provide care to victims of sexual assault and more effort is needed with regards to service provision